Comparison of power system flow analysis methods of IEEE 5-bus system - Harpreet Kaur Channi; Ramandeep Sandhu; Nimay Chandra Giri; Parminder Singh; Fathy Abdelaziz Syam (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Load flow analysis is a crucial tool used by electrical engineers for simulating the power system. It is aimed at examining the most possible way of operating and controlling a power system and the exchange of power flow within the power system. For the economic and optimal operation of power systems, the most essential task is to find the most feasible solution technique suitable and efficient for the study of power generation, transmission, and distribution. There are various power flow study solution techniques, and for some solution techniques, the simulation of the system can take a long time, which prevents the simulator from attaining a higher accuracy result for the power flow simulation due to the interrupting rise and fall in power demand from the consumer, which also affects the power generation as well. This paper discusses the comparison of various techniques used in load flow studies with the assistance of a small power system with five buses. The numerical solution techniques used are the fast decoupled load flow solution technique, the Gauss-Seidel solution technique, and the Newton-Raphson solution technique for a power flow study solution on an IEEE 5-bus using MATLAB/Simulink.